Beyond the Babylonian trauma theories of language and modern culture in the German-Jewish context - Hartung, Gerald (New studies in the history and historiography of philosophy ;, 2018)
The series publishes monographs and essay collections devoted to the history of philosophy as well as studies in the theory of writing the history of philosophy. A special emphasis is placed on the contextualization of philosophical historiography into the areas of the history of science, culture, and the wider scope of intellectual history.